Neural Hedgehog signaling maintains stem cell renewal in the sensory touch dome epithelium - Xiao, Ying (Proc Natl Acad Sci U S A, 2015)
The touch dome is a highly patterned mechanosensory structure in the epidermis composed of specialized keratinocytes in juxtaposition with innervated Merkel cells. The touch dome epithelium is maintained by tissue-specific stem cells, but the signals that regulate the touch dome are not known. We identify touch dome stem cells that are unique among epidermal cells in their activated Hedgehog signaling and ability to maintain the touch dome as a distinct lineage compartment. Skin denervation reveals that renewal of touch dome stem cells requires a perineural microenvironment, and deleting Sonic hedgehog (Shh) in neurons or Smoothened in the epidermis demonstrates that Shh is an essential niche factor that maintains touch dome stem cells. Up-regulation of Hedgehog signaling results in neoplastic expansion of touch dome keratinocytes but no Merkel cell neoplasia. These findings demonstrate that nerve-derived Shh is a critical regulator of lineage-specific stem cells that maintain specialized sensory compartments in the epidermis.